Pulzni laserji - Benko Loknar, Martina (Matrika, 2016)
The article begins with a look at milestones in the history of the laser. Further on, a detailed description of absorption, spontaneous and stimulated emission is given; these are all processes which are essential to the understanding of lasers and their applications. The article includes laser light properties and various types of lasers and also a representation of a technique, used to generate short laser pulses. In the conclusion, applications and fundamental characteristics of pico- and femtosecond lasers are added.
Keywords: delovanje laserjev; functioning; laserji; lasers; pulse lasers; pulzni laserji